Correlation of membrane fouling with topography of patterned membranes for water treatment - Won, Young-June (2017)
Particle depositions on patterned membrane surface were experimentally measured and compared with those of non-patterned membranes. Prism patterns introduced to membrane surface significantly reduced particle deposition. A larger pattern was less effective against particle deposition than a smaller pattern under low Reynolds number, but was very successful in mitigating particle deposition under high Reynolds number at faster crossflow velocity. The particle deposition and anti-fouling mechanisms were analyzed using computational fluid dynamics simulation. A vortex was formed in the valley region between prism patterns, proposing that particles entering the valley region because of permeation drag had a chance to return back to bulk crossflow stream during flowing along with the vortex. The distance between the vortex and bulk stream was shorter under high Reynolds number than under small Reynolds number, suggesting that the return of particles in the valley region into the bulk stream was quite enhanced by increasing crossflow velocity. To further mitigate particle deposition on the valley region, new patterns were developed by introducing intervals to prism patterns and showed much improvement in antifouling ability by enhancing the vortex and reducing the portion of permeation stream in the valley region.